Desain Awal Analog Front-End Optical Transceiver untuk Aplikasi Visible Light Communication - Trio Adiono; Syifaul Fuada; Angga Pratama Putra; Yulian Aska (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Analog Front-End (AFE) is a part of physical layer (PHY) at Visible Light Communications (VLC) system which has important things to transmit and receive the data. This research is a preliminary study in designing AFE transceiver which consists of LED driver and Trans-impedance Amplifier (TIA). The results are used as advanced reference design of AFE system and also to determine the modulations range (analog as well as digital). The design verification is based on data transmission which generated by signal generator. Square wave signal is used as digital modulation representative, and sinusoid signal as analog modulation representatitive. The range of VLC channels is about 50 cm with 0o angle. The result shows that digital modulation bandwidth is about 1 KHz to 10 KHz frequency, and analog modulation bandwidth is from 200 KHz to 600 KHz. We also find a significant impact by adding 1 pF capacitor to reduce noise gain. Furthermore, color filter testing is performed to investigate the design performance.